Correlation of cancer treatment related fatigue with biochemical & hormonal profile a prospective study - Biswal, Biswa Mohan; Kumaraswamy, N.; Mumtaz, Mallik (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
Background: Cancer treatment using chemotherapy or radiotherapy results in considerable cancer treatment related fatigue. Fatigue can induce significant stress causing hormonal alteration through hypothalamic pituitary axis leading to change in the internal milieu. We evaluated hormonal and biochemical profile to find out a putative corr~lation. Materials & Method: Fifty two histopathology documented cases of cancer patients were subjected to Pipers Fatigue Score (PFS) and blood test for hormone and other biochemical parameters before and after radiotherapy and chemotherapy treatment. Human growth hormone, adenocorticotrophic hormone, thyroid stimulating hormone and serum free cortisol level were evaluated along with routine biochemical analysis before and after anticancer treatment. The individual fatigue score were compared with individual hormone levels and other biochemical parameters. Results: Fifty two cancer patients planned for anticancer therapy completed initial pretreatment evaluation however post treatment assessment was not possible in 8 cases as they died during therapy. There were 20 males and 32 females in the study with a median age of 50 years (range15-78 years). The stage distribution was as stage-1 (12°k), stage-11 (17°.4>), stage-Ill (44%) and stage-IV (26°/o).The primary cancer were in breast (19°/o), sarcomas (9°/o), head and neck (19°k), gynecological (19°/o) and miscellaneous sites (14o/o). The individual fatigue score were behavioral severity (26.6°.4>), affective meaning (28°/o), sensory (22.2%), cognitive mood (8.8%) and total score (22.2°.4>) respectively. There were significant rise in the fatigue score followi~g chemotherapy and radiotherapy. The serum human growth hormone and cortisol were positively correlated whereas serum TSH level was negatively correlated with fatigue. Conclusions: Cancer treatment related fatigue is a multidimensional event that affect stress hormonal ·milieu. The human growth hormone and corticotrophins were affected among cancer patients suffering from cancer treatment related fatigue. Probably this finding may help to improve therapeutic intervention in the management fatigue in cancer